PERBANDINGAN KEJADIAN ANEMIA PADA IBU HAMIL YANG TERPAPAR DAN TIDAK TERPAPAR ASAP ROKOK DI DESA TAENG KABUPATEN GOWA - Rosdianah; Anna Khuzaimah; Yusril Ihsanul Mukarram; Aura Audhilla Khadiamsi (Universitas Islam Negeri Alauddin Makassar, 2023)
Anaemia is when the mother's haemoglobin level is below average for gestational age. One of the risk factors for anaemia is exposure to cigarette smoke before and during pregnancy because cigarette smoke contains many harmful substances. This study aims to compare the incidence of anaemia in pregnant women who are exposed to and not exposed to cigarette smoke. The type of research used was cross-sectional, with the sampling method being consecutive sampling and obtaining a sample of 57 samples. The results showed that 29 samples (50.9%) were exposed to cigarette smoke and had anaemia, while 7 samples (12.3%) were exposed to cigarette smoke but did not. For samples not exposed to cigarette smoke but had anaemia, three samples (5.2%) and 18 samples (31.6%) were not exposed to cigarette smoke and did not experience anaemia. The conclusion from the results of this study is that the incidence of anaemia will be higher in pregnant women exposed to cigarette smoke compared to those not exposed to cigarette smoke.